2017
DOI: 10.1371/journal.pone.0177361
|View full text |Cite
|
Sign up to set email alerts
|

First detection of foot-and-mouth disease virus O/Ind-2001d in Vietnam

Abstract: In recent years, foot-and-mouth disease virus (FMDV) serotype O, topotype Middle East-South Asia (ME-SA), lineage Ind-2001d has spread from the Indian subcontinent to the Middle East, North Africa, and Southeast Asia. In the current report, we describe the first detection of this lineage in Vietnam in May, 2015 in Đắk Nông province. Three subsequent outbreaks caused by genetically related viruses occurred between May–October, 2015 after which the virus was not detected in clinical outbreaks for at least 15 sub… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

2
25
1

Year Published

2017
2017
2021
2021

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 27 publications
(28 citation statements)
references
References 24 publications
2
25
1
Order By: Relevance
“…Recent estimates suggest that total economic losses in India attributed to FMD range from $1,800 to 2,100 million USD annually (Singh, Prasad, Sinha, & Verma, ). Additionally, many viral strains isolated in the Middle East and South‐East Asia have ancestral roots in India (Arzt et al., ; Bachanek‐Bankowska, Wadsworth, Thapa, King, & Knowles, ; Brito, Rodriguez, Hammond, Pinto, & Perez, ; Vu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Recent estimates suggest that total economic losses in India attributed to FMD range from $1,800 to 2,100 million USD annually (Singh, Prasad, Sinha, & Verma, ). Additionally, many viral strains isolated in the Middle East and South‐East Asia have ancestral roots in India (Arzt et al., ; Bachanek‐Bankowska, Wadsworth, Thapa, King, & Knowles, ; Brito, Rodriguez, Hammond, Pinto, & Perez, ; Vu et al., ).…”
Section: Introductionmentioning
confidence: 99%
“…Secondly, some reported cases of FMD were misdiagnosed with other diseases (e.g. swine vesicular diseases and bovine viral diarrhoea virus)(Duong, Alenius, Huong, & Bjorkman, 2008;Liu, Li, Liang, Li, & Cui, 2019;Reid, Ferris, Hutchings, King, & Alexandersen, 2004;Vu et al, 2017) as approximately only 20%-30% of cases (expert opinion) were confirmed by national laboratories. Therefore, it is necessary to strengthen the national surveillance system with laboratory confirmation.…”
mentioning
confidence: 99%
“…Mortalities were recorded mostly in lambs and kids; both of which had CFR values as high as 77%, while, in two cattle farms, CFR values for young calves ranged between 11% and 19%. In the Jordanian outbreak, sheep and goats were affected by FMD unlike what was reported in Vietnam, where the Ind2001d sublineage did not appear to cause an FMD‐related clinical outcome in sheep and goats (Vu et al, ). During the 2013 and 2015 FMD outbreaks of the Ind2001d sublineage in Saudi Arabia and Morocco, respectively, all samples collected were from cattle (WRLFMD, , ).…”
Section: Discussionmentioning
confidence: 97%